Menganalisa Power Leadership PT. PNM Cabang Samarinda - Al Muarafah, M Akbar; Mildawani (Jurnal Online Manajemen ELPEI, 2024)
This research aims to examine the application of Power Leadership which is an important element in the success of companies, especially PT. PNM Samarinda Branch. This study uses a qualitative descriptive method to examine more deeply the types of Power Leadership. The informants as the subjects of the study were one Manager, one Unit Head, and two staff members who were selected based on their uniqueness, namely Gen Z. Findings from the study showed that power affects employee behavior and work performance and fosters a positive work culture. The leadership strength applied by the leadership of PT. PNM Samarinda Branch is; The power of rewards, the power of legitimacy, the power of references, the power of experts.